بناء نموذج تحليلي للتأخير في الشبكة المضمّنة على الشريحة باستخدام نظرية الترتيل - دنده رضوان; العاتكي طلال; قسام روني (Latakia University Journal -Engineering Sciences Series, 2019)
The Network-on-Chip architectures suffer from the difficulty of allocating processing resources in the execution time to suit the complex applications implemented on these architectures. In the event of any change in the input traffic, there is no change in the architecture level and its configuration. So it will be an inefficient running of the application on the architecture. Researches are currently modeling the input rates for data and determining service times required to implement application tasks [1]. These researches are limited to the NoC mechanisms of handling with different models but without any modifications to the architecture to suit these models. Therefore, this research propose modifications on the mathematical models used to include changes in the queue lengths and resource utilization rates to ensure the compatibility with application status. These status are classifying with multiple classifications close to the application tasks and can be included within the architecture in such a way as to ensure the effective operation of the class occasion. The research resulted in a reduction of about 10% of the latency for low input rates with the possibility of dealing more with the increasing of input rates, as well as opening up the application to reflect its effect in a way that can be improved on the architecture through the classification included in the mathematical model. تعاني معماريات الشبكات المضمّنة على الشريحة من صعوبة توزيع موارد المعالجة في زمن التنفيذ بما يتناسب مع التطبيقات المعقدة المنفذة على هذه المعماريات، حيث أنه عند حدوث أي تغير في الدخل لا يؤدي إلى أي تغير على مستوى المعمارية والإعدادات الخاصة بها وإنما سيبقى التعامل حسب الإعدادات المثبتة سابقاً وبالتالي سيكون هناك تشغيل غير فعال للتطبيق على المعمارية. تقوم حالياً الدراسات بنمذجة معدلات الدخل للبيانات وتحديد أزمنة الخدمة المطلوبة لتنفيذ مهام التطبيق [1]، تقتصر هذه الدراسات على آليات تعامل الشبكات المضّمنة على الشريحة مع اختلاف هذه النماذج ولكن بدون أي تضمين لتعديلات ضمن المعمارية لتتناسب مع هذه النماذج. لذلك تم في هذا البحث اقتراح تعديلات على النماذج الرياضية المتبعة لتضمين تعديلات في أطوال الرتل ومعدلات استخدام الموارد وبشكل يؤمن توافق مع حالات التطبيق، حيث يتم تصنيف هذه الحالات بأصناف متعددة قريبة من مهام التطبيق من جهة وقابلة للتضمين ضمن المعمارية بشكل يؤمن التشغيل الفعال للصنف بأزمنة تأخير مناسبة. توصل البحث إلى تخفيض حوالي 10% من أزمنة التأخير بالنسبة لمعدلات دخل منخفضة مع إمكانية التعامل بشكل أكبر مع زيادة معدلات الدخل وكذلك فتح المجال للتطبيق ليعكس أثره بشكل يكون قابلاً للتحسين على المعمارية من خلال التصنيف المضمن بالنموذج الرياضي.